The Role of Al-Qur'an Hadith Teachers in Fostering Students' Curiosity Character at MAS Muhammadiyah 01 Medan - Mhd. Ihsanul Fikri; Syamsu Nahar; Meyniar Albina (Cipta Pustaka Nusantara, 2026)
This study aims to analyze the strategies employed by Al-Qur'an Hadith teachers in fostering students' curiosity character and to evaluate the outcomes of this character development at MAS Muhammadiyah 01 Medan. Character education, particularly the development of curiosity, is a crucial aspect in shaping students to become critical and independent learners. This research adopts a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. The research subjects include Al-Qur'an Hadith teachers and 14 students from Grade XI of the Science and Social Studies streams. The findings indicate that the implemented strategies include active learning methods such as Inquiry-Based Learning and Problem-Based Learning, the creation of a conducive learning environment, the provision of appreciation and motivation, as well as religious programs such as the Intensive Islamic Studies Program (Kajian Islam Intensif/KII). The development of students' curiosity shows significant results, evidenced by increased activeness in asking questions, independent information seeking, and greater enthusiasm for learning. Approximately 70% of students demonstrate high indicators of curiosity, although challenges remain among students with low learning motivation and limited financial resources to support varied learning activities. The implications of this study suggest that integrating active learning models with religious-based programs can serve as an effective approach for strengthening students' curiosity character in Islamic education contexts. This study also provides practical guidance for teachers and educational institutions in designing student-centered learning environments that foster critical thinking, intrinsic motivation, and sustainable character development based on Islamic values.